2012
DOI: 10.17221/97/2010-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the montane taiga forests of West Khentii, Northern Mongolia

Abstract: Studies were undertaken to investigate the composition, structure and diversity of four different types of North Mongolian montane forest near the southern border of the taiga. These forest types, classified as willow-poplar, larch-birch, spruce-fir and Siberian-pine forests, were found to be significantly different with respect to the elevational gradient. In the study area, two fire regimes could be distinguished at lower and drier elevations, frequent surface fires resulted in less diverse forests comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Since the mid 90ies researchers conducted comprehensive interdisciplinary field work in international teams (Mühlenberg 2012), which lead in some cases even to the validation of new species for Mongolia or even new to science (see for example Bayartogtokh (2000). Undisturbed forests contain also higher biodiversity compared to frequently disturbed forests as indicated by studies focusing on forest structure in disturbed light taiga and undisturbed dark taiga forest stands (Gradel and Mühlenberg 2011;Mühlenberg et al 2012). These forests are also more productive in terms of basal area and volume (Mühlenberg 2012), which is in compliance with recent conclusions about a diversityproductivity relation on global level (Liang et al 2016).…”
Section: Lesson Learned High Biodiversity In the Mountain Forest Steppementioning
confidence: 99%
See 2 more Smart Citations
“…Since the mid 90ies researchers conducted comprehensive interdisciplinary field work in international teams (Mühlenberg 2012), which lead in some cases even to the validation of new species for Mongolia or even new to science (see for example Bayartogtokh (2000). Undisturbed forests contain also higher biodiversity compared to frequently disturbed forests as indicated by studies focusing on forest structure in disturbed light taiga and undisturbed dark taiga forest stands (Gradel and Mühlenberg 2011;Mühlenberg et al 2012). These forests are also more productive in terms of basal area and volume (Mühlenberg 2012), which is in compliance with recent conclusions about a diversityproductivity relation on global level (Liang et al 2016).…”
Section: Lesson Learned High Biodiversity In the Mountain Forest Steppementioning
confidence: 99%
“…Based on criteria related to human alteration, remoteness and the level of fragmentation the remote sensing based worldwide intact forest landscape mapping and monitoring (Potapov et al 2008; indicated that in Mongolia especially the Khentii Mountains have still a considerable portion of untouched, so called intact forest landscapes, which is however, constantly decreasing, especially due to fire impact (Potapov et al 2017). Forest types that are often mentioned as valuable for different conservation reasons are especially types of riparian forests (Bei et al 2003;Mühlenberg et al 2004) and types of dark conifer forests (Dulamsuren 2004;Gradel and Mühlenberg 2011;Mühlenberg et al 2012). Abies sibirica is naturally rare and limited to the two main forest regions in Northern Mongolia, namely around Lake Khuvsgul and the Khentii Mountain range (Dulamsuren 2004).…”
Section: Lesson Learned High Biodiversity In the Mountain Forest Steppementioning
confidence: 99%
See 1 more Smart Citation
“…Siberian larch is one of the prevailing wood species in forests of the distinctive mountain forest steppe in Northern Mongolian, a transition zone between the northern boreal forest of the Siberian taiga to the dry steppes of Inner Asia (Mühlenberg et al 2012). Sun exposure and other microclimatic conditions combined with the prevailing disturbance regime, which is fire (MET 2016), are decisive factors for site-specific vegetation: the northern slopes are largely forested, whereas the southern slopes are dominated by steppe vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…We examined the tree species diversity, tree qualitative and quantitative parameters as well as abundance of herbal species and the overall coverage (Mühlenberg et al 2012). Using the Šimek method (Š imek 2014), qualitative parameters are presented in Table 1; quantitative parameters are given in Table 2.…”
Section: Field Of Researchmentioning
confidence: 99%